2020
DOI: 10.1101/2020.07.06.190413
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of Drug-like Ligands for the Mac1 Domain of SARS-CoV-2 Nsp3

Abstract: ABSTRACTThe Mac1 domain of the multifunctional SARS-CoV-2 non-structural protein 3 (nsp3) is a potential COVID-19 drug target because it is suspected to enhance the ability of the virus to evade the human immune system. The SARS-CoV-2 Mac1 domain binds ADP-ribose and proteins harboring this important post-translational modification. Small molecules that bind the Mac1 domain in place of ADP-ribose might therefore be useful as molecular probes or scaffolds for antiviral drug disc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Because of their ready availability in useful amounts, most of these experiments focused on the docking hits. For DSF, in agreement with previous reports for this domain ( 24 ), we observed substantial elevation of the apparent melting temperature (Tm a ) of Nsp3 Mac1 upon addition of its known binding partner, ADP-ribose ( Fig. 9 C,D,G).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Because of their ready availability in useful amounts, most of these experiments focused on the docking hits. For DSF, in agreement with previous reports for this domain ( 24 ), we observed substantial elevation of the apparent melting temperature (Tm a ) of Nsp3 Mac1 upon addition of its known binding partner, ADP-ribose ( Fig. 9 C,D,G).…”
Section: Resultssupporting
confidence: 92%
“…While this inhibitor showed on-target activity in cells, its unique allosteric binding site is difficult to translate to other macrodomains. While potential Mac1 inhibitors have emerged with the advent of SARS-CoV-2 (23)(24)(25)(26)(27), their binding mechanisms and efficacy remain unclear. The lack of a biochemical assay specific for Mac1 has hindered their development.…”
Section: Introductionmentioning
confidence: 99%
“…The structural (Figure 4) and functional perspectives of the SARS-CoV-2 protein mutations reported here provide some useful information for the therapeutics. The PL-pro domain and macrodomain of NSP3 can be potential drug targets as they are comparatively resistant to mutations 67 . Occurrence of S25L and S26F in NSP7 are at the proximity of NSP8 interface, NSP8 mutations M129I (at the interface of NSP8-NSP12) and R51C/L (at the RNA interacting region) and proximity of P323L-NSP12 to the NSP8 binding site indicate a possible modulation in the viral replication mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Since the role of macrodomains in pathogenesis is essential, it appears that their inhibition may help to reduce the viral load and facilitate recovery. Therefore, these proteins might be attractive targets for the development of small-molecule antivirals, assuming that highly selective compounds could be found that discriminate between viral and human macrodomains (Virdi et al, 2020). As a step towards this goal, we have determined the crystal structure of SARS-CoV-2 ADRP in multiple states: in the apo form and in complexes with 2-(N-morpholino)ethanesulfonic acid (MES), AMP and ADPr.…”
Section: Introductionmentioning
confidence: 99%